2015
DOI: 10.2460/ajvr.76.9.755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of hydrocodone-acetaminophen and tramadol for control of postoperative pain in dogs following tibial plateau leveling osteotomy

Abstract: Overall, differences in pain scores between dogs that received hydrocodone-acetaminophen or tramadol were minor. The percentage of dogs with treatment failure in both groups was considered unacceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…Reported complications associated with ESWT include mild bruising, redness, transient superficial pain at the treatment site, and the requirement for sedation or general anesthesia for treatment . Subjective pain evaluation 24 hours after surgery in this study may not have been of sufficient resolution to detect differences between treatments, although the rubric used is well established for comparison of postoperative comfort levels . More objective forms of pain evaluation, such as kinetic gait, mechanical threshold testing with an algometer, or stance analysis, could have been performed …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reported complications associated with ESWT include mild bruising, redness, transient superficial pain at the treatment site, and the requirement for sedation or general anesthesia for treatment . Subjective pain evaluation 24 hours after surgery in this study may not have been of sufficient resolution to detect differences between treatments, although the rubric used is well established for comparison of postoperative comfort levels . More objective forms of pain evaluation, such as kinetic gait, mechanical threshold testing with an algometer, or stance analysis, could have been performed …”
Section: Discussionmentioning
confidence: 99%
“…Pain was assessed via the short form of the Glasgow Composite Pain Scale, which includes six behaviors: vocalization, attention to wound, mobility, response to touch, demeanor, and posture/activity . Although it is used to measure pain in dogs, the scale is subjective and may be influenced by how the dog interacts with observers, differences in interpretation of scoring criteria among observers, and varying thresholds of pain tolerance among dogs …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent trials have indicated that oral, epidural, and parenteral administration of tramadol does not produce significant concentrations of the opioid M1 metabolite (O‐desmethyltramadol) in dogs which are required to produce an opioid effect in other species (Matthiesen et al ., ; Vettorato et al ., ; KuKanich & Papich, ; Kögel et al ., ; Benitez et al ., ). The drug alone did not provide adequate postoperative analgesia in dogs undergoing tibial plateau leveling osteotomy (Davila et al ., ; Benitez et al ., ). In addition, the nonopioid mechanisms of action of tramadol produced limited antinociception in an acute pain model in dogs (Kögel et al ., ).…”
Section: Novel Opioid Therapiesmentioning
confidence: 97%